32.0k views
3 votes
If f(x) = x^4 - 2x³ + 6x-1, What is f (-2)

HELPP!!

User ASk
by
5.5k points

2 Answers

2 votes

Answer:

f(-2) = 19

Explanation:

Given function:


f(x)=x^4-2x^3+6x-1

To find f(-2), substitute x = -2 into the given function.


\begin{aligned}x=-2 \implies f(-2)&=(-2)^4-2(-2)^3+6(-2)-1\\&=16-2(-8)+6(-2)-1\\&=16+16-12-1\\&=32-12-1\\&=20-1\\&=19\end{aligned}

Therefore, f(-2) = 19.

User James Ikubi
by
4.7k points
1 vote

Answer:

f(- 2) = 19

Explanation:

to evaluate f(- 2) , substitute x = - 2 into f(x)

f(2) =
(-2)^(4) - 2(- 2)³ + 6(- 2) - 1

= 16 - 2(- 8) - 12 - 1

= 16 + 16 - 13

= 32 - 13

= 19

User Dmitry Ionash
by
4.5k points